Bodies in dissent between the political, the private and the technological - Pagnes, Andrea (Repertório, 2023)
The article resumes the author’s lecture Bodies in Dissent. Regarding Live art and performance art, issues such as embodiment and identity are tackled, enriched by excerpts of a recent conversation the author had with Australian performance artist Stelarc about how technology is affecting the human body as a cognitive tool, leading us to reconsider the meaning of human existence.